2022
DOI: 10.3390/su142013328
|View full text |Cite
|
Sign up to set email alerts
|

Demand Response Transit Scheduling Research Based on Urban and Rural Transportation Station Optimization

Abstract: To reduce the operating cost and running time of demand responsive transit between urban and rural areas, a DBSCAN K-means (DK-means) clustering algorithm, which is based on the density-based spatial clustering of applications with noise (DBSCAN) and K-means clustering algorithm, was proposed to cluster pre-processing and station optimization for passenger reservation demand and to design a new variable-route demand responsive transit service system that can promote urban–rural integration. Firstly, after prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Li et al introduce a flexible ODT and develope a public transit scheduling model to meet public transit travel needs. The results show that the flexible ODT service can reduce operating costs by 9.5% and running time by 9% [10]. Nourbakhsh and Ouyang compare the performance of flexible route transit and traditional transit for different demand levels and found that the former usually has the lowest system cost when the demands mild [11].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al introduce a flexible ODT and develope a public transit scheduling model to meet public transit travel needs. The results show that the flexible ODT service can reduce operating costs by 9.5% and running time by 9% [10]. Nourbakhsh and Ouyang compare the performance of flexible route transit and traditional transit for different demand levels and found that the former usually has the lowest system cost when the demands mild [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…where ω is the unit time value of travelers before boarding the bus (Unit: RMB/h), including the walking time to the stop and the waiting time at the stop; T walk and T wait represent the walking time and waiting time for all travelers who board at both normal stops and on-demand stops (Unit: h); t walk oi and t walk os denote the walking time (Unit: h) from the origin o to the nearest normal stop i and to the nearest on-demand stop s, respectively, as shown in Equations ( 5) and ( 6); t wait idw and t wait sdw represent the average waiting time (Unit: h) of travelers at the normal stop i and the on-demand stop s, respectively, during the time window w, as shown in Equations ( 7) and ( 8); and λ odwi and λ odws are, respectively, the average number of travelers waiting at normal stop I and on-demand stop s who travel from origin o to destination d in time window w, as shown in Equations ( 9) and (10).…”
Section: Upper Model: Optimization Of On-demand Servicementioning
confidence: 99%
“…For high-dimensional data, this algorithm may reduce the clustering accuracy to some extent. However, DBSCAN does not require a predetermined number of clusters [41,42]. In the clustering of urban nodes, due to the small number and dimension of nodes, the precision reduction will hardly be affected.…”
Section: Research On Dbscanmentioning
confidence: 99%
“…Compared to GA, simulated annealing (SA) [30,31] has a global search superiority by which fewer results are trapped in the local optimum. SA is derived from the annealing process of solid materials in physics starting with an initial temperature and followed by a temperature decrease.…”
Section: Simulated Annealingmentioning
confidence: 99%